GSGP-C++ 2.0 - Castelli, Mauro (2019)
Castelli, M., & Manzoni, L. (2019). GSGP-C++ 2.0: A geometric semantic genetic programming framework. SoftwareX, 10, [100313]. https://doi.org/10.1016/j.softx.2019.100313